Cartilha Educativa Ilustrada: orientações para acompanhantes de crianças submetidas a intervenções cirúrgicas - Torezan, Graciele (Universidade do Vale do Rio dos Sinos, 2016)
This study started to the preparation of an educational folder about the environment and surgical procedure for the companions who have children undergoing surgery. This is a descriptive study with qualitative approach, held in the unit of the surgical center (DC), a private hospital in the city of Caxias do Sul, state of Rio Grande do Sul. The study gathered 18 caregivers of children who were being undergoing surgery in DC. To collect the data I've used a semi-structured interview which included topics facing the trials and knowledge of caregivers about the environment and the surgical procedure that the child was being submitted, the analysis found the content was the subject type. Of the 18 research participants one is male, the father, and 17 females, mothers. The ages ranged from 23 to 46 years, with a degree of complete elementary school education to complete higher education. They resulted in two categories: first, feelings experienced by caregivers, with two subcategories - fear of the unknown; nervousness, apprehension and anxiety. Second category, contributions from companions improved customer service, with two subcategories - clearing the surgical process; and adequate reception space. Participants of this study point out that, surgical process is accompanied by many negative feelings, and that these could be minimized if previously had to clarify this process, stressed that the medical professional is the main informant about the surgery itself, only one participant cited other professional as an informant, nursing was not mentioned. Participants suggested to several ways to improve the service during its passage through DC, highlighting the presence of educational material for consultation, a specific place waiting in the DC for children and companions and playful material for distraction of children. The results of this study allowed us to consider that the lack of information about the surgical process of companions is a reality at the study site. Thus, health institutions should review their processes in an attempt to deploy host protocols to the children and their companions in the DC unit. The construction of the educational folder about the environment and surgical procedure will be an important tool for guidance and clarification for the companions who have children undergoing surgical procedures.
Keywords: Centro cirúrgico; Sentimentos; Acompanhantes; Cartilha; Surgical center; Feelings; Escorts; Primer; ACCNPQ::Ciências da Saúde::Enfermagem